A New Chronology of Late Quaternary Sequences From the Central Arctic Ocean Based on "Extinction Ages" of Their Excesses in 231Pa and 230Th. (26th December 2017) - Hillaire‐Marcel, C.; Ghaleb, B.; de Vernal, A.; Maccali, J.; Cuny, K.; Jacobel, A.; Le Duc, C.; McManus, J.
Abstract: Merging the late Quaternary Arctic paleoceanography into the Earth's global climate history remains challenging due to the lack of robust marine chronostratigraphies. Over ridges notably, low and variable sedimentation rates, scarce biogenic remains ensuing from low productivity and/or poor preservation, and oxygen isotope and paleomagnetic records differing from global stacks represent major impediments. However, as illustrate here based on consistent records from Mendeleev‐Alpha and Lomonosov Ridges, disequilibria between U‐series isotopes can provide benchmark ages. In such settings, fluxes of the particle‐reactive U‐daughter isotopes 230 Th and 231 Pa from the water column, are not unequivocally linked to sedimentation rates, but rather to sea‐ice rafting and brine production histories, thus to the development of sea‐ice factories over shelves during intervals of high relative sea level. The excesses in 230 Th and 231 Pa over fractions supported by their parent U‐isotopes, collapse down sedimentary sequences, due to radioactive decay, and provide radiometric benchmark ages of approximately 300 and 140 ka, respectively. These "extinction ages" point to mean sedimentation rates of ∼4.3 and ∼1.7 mm/ka, respectively, over the Lomonosov and Mendeleev Ridges, which are significantly lower than assumed in most recent studies, thus highlighting the need for revisiting current interpretations of Arctic lithostratigraphies in relation to the global‐scale late Quaternary climatostratigraphy. Plain Language Summary: The Arctic Ocean represents a major component of the Earth climate system notably with regard to the Arctic amplification and freshwater fluxes toward the global ocean. Understanding its role versus the global climate history of the recent glacial/interglacial cycles remains challenging due to the lack of robust chronology of marine sedimentary archives. In the present study, we demonstrate that the decay of Uranium series isotopes in sediments from major Arctic ridges provide benchmark ages for the last ∼300, 000 years and support the concept of a "sediment‐starved" environment in the central Arctic Ocean. Key Points: New chronology of late Quaternary marine sequences from the central Arctic Mean sedimentation rates of the order of millimeters per thousand years over ridges Highly discontinuous ice‐rafted sedimentation over ridges with gaps